Debating Arab Authoritarianism: Dynamics and Durability in Nondemocratic Regimes by Oliver Schlumberger, ed. (Stanford, California: Stanford University Press, 2007. 345 pages.) (American Journal of Islam and Society, 2009)
The Middle East has long contended with the title of the region most lackingin democratic state structures, and while several countries endeavor toenforce a form of democracy, yet others preserve the frameworks that efficientlysustain their monarchies, revenue, and power status in the area. Thetwin questions of how and why democracy has proved elusive in theMiddleEast forms the crux of the collection of essays comprised within Schlumberger’stome: Debating Arab Authoritarianism: Dynamics and Durabilityin Nondemocratic Regimes.Spanning Morocco to Oman, via Egypt, Jordan, and Saudi Arabia, theauthoritarian mode of governance is surveyed through an assessment of thedurability of regimes, the role of Islamist political parties, intra-regimedynamics, and the economic aspects of political reform. Divided into foursections, the book’s structure incorporates key elements of Arab authoritarianism:“State-Society Relations and Political Opposition,” “The Regimes,”“The Economy and the Polity,” and “The InternationalArena.” That the sectionsretain a subtle reluctance to address the link between the repressivecapacities ofArab states and their longevity, as well as the concept that Islamis incompatible with democracy, is conspicuous, yet prudent. Far fromretreadingworn theories, the contributors provide fresh conceptual and comparativeanalyses of individual countries and the region on a wider level, inaddition to prospects for the respective regimes ...